The Dynamic Tensions Of The Postmodern Self: Fragmenting Identities In The Selected Short Stories Of Karim Raslan And Dina Zaman - Babu Ali, Shaik Husseinudin (2018)
This study focuses on the postmodern ‘self’ in the portrayal of the characters in Karim Raslan’s and Dina Zaman’s selected short stories. It explores the dynamic tensions and the impact of postmodernism on the ‘self’ which result in the fragmentation of the ‘self’. The focus of the analysis of this study involves the construction of the postmodern ‘self’, how the postmodern ‘self’ subverts and negotiates cultural, religious, gender and sexual identities within the context of postmodern Malaysia. It also explores the strategies that are employed by the authors to subvert dominant ideas pertaining to culture, religion, gender and sexuality in their stories.